2018
DOI: 10.1089/thy.2018.0129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radioactive Iodine Therapy on Ovarian Reserve: A Prospective Pilot Study

Abstract: AMH is considered an important marker of ovarian reserve. Ovarian reserve decreased after RAI therapy. More attention may be needed when considering RAI therapy for patients with reduced ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 30 publications
3
31
0
2
Order By: Relevance
“…In contrast, five patients who were treated for Graves' disease with a mean activity of 13 mCi did not have a decrease in AMH (40). The second study, from Turkey, evaluated 33 women, at a mean age of 31 years, after receiving RAI after thyroid hormone withdrawal at a mean activity of 111 mCi (41). This study showed similar findings, with significant drop of AMH at 3 months, with only slight recovery by 12 months.…”
Section: Radioactive Iodinementioning
confidence: 72%
See 1 more Smart Citation
“…In contrast, five patients who were treated for Graves' disease with a mean activity of 13 mCi did not have a decrease in AMH (40). The second study, from Turkey, evaluated 33 women, at a mean age of 31 years, after receiving RAI after thyroid hormone withdrawal at a mean activity of 111 mCi (41). This study showed similar findings, with significant drop of AMH at 3 months, with only slight recovery by 12 months.…”
Section: Radioactive Iodinementioning
confidence: 72%
“…This study showed similar findings, with significant drop of AMH at 3 months, with only slight recovery by 12 months. Women over the age of 30 years had higher decreases in AMH than younger women (41).…”
Section: Radioactive Iodinementioning
confidence: 84%
“…In both studies, the interval between thyroidectomy and RAI administration and AMH sample collection was of several months: more than 36 months in the Acibucu et al study [14] and 5 years on average in our study [15]. Recently, Yaish et al [16] and Evranos et al [17] designed similar studies in which AMH was evaluated before and 3-12 months after RAI administration in DTC females. These studies showed a significant decrease in AMH levels, with lower levels 3 months after RAI, and an increasing trend in the following months, though pre-RAI levels were not reached by the 12-month evaluation.…”
Section: Introductionmentioning
confidence: 60%
“…Radiation therapy was also recognized as highly ovario-toxic even at low doses, associated to 149 extremely low or undetectable AMH dosages in the post-treatment patients [55]. In 2018, a prospective pilot study showed decreased ovarian reserve of thyroid carcinoma patients after radioiodine therapy, the median AMH levels being 3.25 (0.32-17.42), 1 (0.01-3.93), 1.13 (0.08-6.12), and 1.37 (0.09-6.1) ng/ml before and in the 3rd, 6th, and 12th month after therapy [56]. A prospective study showed that AMH levels of 42 pediatric females with cancer who had underwent fertility preservation procedures dropped by approximately 40-50%, and their AMH levels after anti-cancer and ovarian folliculus preservation therapy increased until approximatly10 years later and then decreased [57].…”
Section: Discussionmentioning
confidence: 97%